Letters to Florence O'Donoghue from various individuals (A - Bannon) in response to queries and newspaper advertisements seeking information on Liam Lynch and in response to his serial publication of 'No Other Law' - O'Donoghue, Florence, 1895-1967 (1953)
Correspondents are Patrick Ahern, John Armstrong, Seamus Babington and Thomas Bannon.
Keywords: O'Donoghue, Florence, -- 1895-1967 -- Correspondence; Lynch, Liam, -- 1893-1923; Irish Republican Army; Ireland -- History -- 1910-1921; Ireland -- History -- 1922-